Microengineered 3D Collagen Gels with Independently Tunable Fiber Anisotropy and Directionality. Issue 4 (10th March 2021) - Ahmed, Adeel; Joshi, Indranil M.; Larson, Stephen; Mansouri, Mehran; Gholizadeh, Shayan; Allahyari, Zahra; Forouzandeh, Farzad; Borkholder, David A.; Gaborski, Thomas R.; Abhyankar, Vinay V.
Abstract: Cellular processes are linked to the alignment (anisotropy) and orientation (directionality) of collagen fibers (i.e., landscape) in the native extracellular matrix (ECM). Given the vital role that cell‐matrix interactions play in regulating biological functions, several microfluidic methods have successfully established anisotropic 3D collagen gels to develop quantitative relationships between structural cues and cellular responses. However, independently tailoring the fiber anisotropy and fiber directionality within a landscape remains a challenge. Here, a user‐friendly microfluidic platform with a non‐uniform channel geometry is used to control the degree of fiber anisotropy and directionality as a function of extensional strain rate and a defined flow path, respectively. New experimental capabilities, including independent control over the degree of fiber anisotropy and directionality, spatial gradients in anisotropy, and multi‐material interfaces, are demonstrated. A channel peel‐off technique provides direct access to the microengineered collagen landscapes, and the alignment of single MD‐MB‐231 cancer cells and monolayers of human umbilical vein endothelial cells (HUVEC) is shown. Finally, the platform's modular capability is highlighted by integrating an ultrathin porous Parylene (UPP) membrane onto the microengineered collagen landscape as a method to control the degree of cell‐matrix interaction. Abstract : A user‐friendly microfluidic platform to microengineer collagen landscapes as a function of extensional strain rate and flow path is presented. New capabilities to independently control fiber anisotropy and directionality, create spatial gradients in anisotropy, and generate multi‐material interfaces are demonstrated. A channel peel‐off technique provides direct access to the collagen gels, and cell responses to the engineered landscapes are shown.